A Distributed Event-Triggered Algorithm for Economic Dispatch Problem over Unbalanced Directed Network - Shi, Xiasheng; Ding, Lifu; Yan, Gangfeng (Chinese Control and Decision Conference, 2020)
In this paper, we design a distributed surplus-based event-triggered algorithm to fix the economic dispatch problem over general directed graph in smart grid. In order to avoid continuous communication, the event-triggered communication mechanism is established, in which each agent only broadcasts its information at their last triggering time, which is controlled by the designed triggering condition, rather of every sampling time. A sufficient condition is developed for guarding the consensus and achieving the optimal solution. That is the network is strongly connected and the necessary parameters are properly designed. Moreover, we offer one case to check the feasibility of above proposed algorithm.